2018
DOI: 10.1111/imcb.12212
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 mediates ER expansion during hyperpolarization of alternatively activated macrophages

Abstract: Although recent evidence has shown that IL‐6 is involved in enhanced alternative activation of macrophages toward a profibrotic phenotype, the mechanisms leading to their increased secretory capacity are not fully understood. Here, we investigated the effect of IL‐6 on endoplasmic reticulum (ER) expansion and alternative activation of macrophages in vitro. An essential mediator in this ER expansion process is the IRE1 pathway, which possesses a kinase and endoribonuclease domain to cleave XBP1 into a spliced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The MR devices use powerful magnets and radiofrequency pulses instead of ionizing radiation. Furthermore, due to recent developments, it is now possible to record functional imaging of organs by using functional MR (fMR) technology (Cheng et al, 2018;Logothetis et al, 2001;Michalopoulos and Bourbakis, 2015;Saignavongs et al, 2017;. Medical imaging technologies now provide an enormous amount of data to the researchers from healthcare area to diagnose the diseases fast and accurately.…”
Section: Introductionmentioning
confidence: 99%
“…The MR devices use powerful magnets and radiofrequency pulses instead of ionizing radiation. Furthermore, due to recent developments, it is now possible to record functional imaging of organs by using functional MR (fMR) technology (Cheng et al, 2018;Logothetis et al, 2001;Michalopoulos and Bourbakis, 2015;Saignavongs et al, 2017;. Medical imaging technologies now provide an enormous amount of data to the researchers from healthcare area to diagnose the diseases fast and accurately.…”
Section: Introductionmentioning
confidence: 99%
“…ER stress-induced transcriptional upregulation of MANF is driven by an ER stress response element (ERSE)-II in the MANF promoter, and is recognized by ATF6 or XBP1s[ 26 , 27 ]. The XBP1 arm of the UPR is thought to play a critical role in enhancing the M2-like macrophage phenotype[ 28 ]. A recent study has shown that damaged retina secretes platelet-derived growth factor-AA (PDGF-AA) that signals to innate immune cells to produce MANF, which promotes macrophage M2 activation and tissue repair[ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…They identified nine specific distinct profiles according the agonist used, and a common transcriptomic signature, which was pertinent to isolate a polarized signature in inflammatory and infectious diseases outside of cancer [68]. Some alternative approaches to microarray such as nanostring method uses directly a panel of genes to measure their variation and may be convenient to investigate macrophage polarization [69]. Whatever the method, gene expression data must be controlled by quantitative RT-PCR, a very sensitive technic that needs low amounts of cells [70].…”
Section: Models Of Macrophage Polarization and Methods Of Studymentioning
confidence: 99%